Faktor dan Strategi Fundamentalisme Agama pada Mahasiswa Muslim - Nur'aini Azizah; Mohamad Sopian; Prasojo Chandra Buana (Jurnal Psikologi Islam dan Budaya, 2021)
Religious-based conflicts often occurred in a country where certain religion became majority. This is an important thing to identify because it will greatly determine the welfare of the people and tolerance in the community. This study aims to explore influential factors and strategies of religious fundamentalism. The method used was qualitative approach. A set of open-ended questions was distributed to 47 Muslim university students in Bandung. The data was analyzed using thematic analysis. Results show that religiocentrism and identity can be the influential factors of religious fundamentalism. Also, they tend to use persuasive approach, religion-based learning, and internalization to implement the fundamentalism. This study contributes to the individual formation of religious fundamentalism, particularly in the context of Indonesian university students.